The Cost of Frailty: Why it’s Matter? - Anung Ahadi Pradana (Jurnal Kesehatan, 2025)
Frailty has emerged as a significant contributor to disability and functional decline among older adults over the past decade. The increasing financial burden and out-of-pocket expenses faced by frail older adults pose a significant challenge to efforts aimed at improving public health. The increasing pattern of healthcare costs associated with frailty among older adults requires particular attention from healthcare professionals. Direct approaches should focus on promoting active engagement and empowering older adults in their daily lives within the community.